Binding of anti-cardiovascular drug to serum albumin: an insight in the light of spectroscopic and computational approaches. Issue 1 (2nd January 2018) - Chandel, Tajalli Ilm; Rabbani, Gulam; Khan, MohsinVahid; Zaman, Masihuz; Alam, Parvez; E. Shahein, Yasser; Hasan Khan, Rizwan
Abstract : Isoprenaline hydrochloride is a potential cardiovascular drug helps in the smooth functioning of the heart muscles. So, we have performed the binding study of ISO with BSA. This study was investigated by UV absorption, fluorescence, synchronous fluorescence, circular dichroism, etc. The analysis of intrinsic fluorescence data showed the low binding affinity of ISO. The binding constant K b was 2.8 × 103 M-1 and binding stoichiometry (n) was approximately one and the Gibb's free energy change at 310 K was determined to be -8.69 kcal mol −1 . Negative Gibb's free energy change shows the spontaneity of the BSA and ISO interaction. We have found ISO-induced alternation in the UV absorption, synchronous fluorescence and CD spectra in the absence and presence of the quencher indicates the complex formation. In synchronous fluorescence, red shift was obtained because of the complex formation of BSA and ISO. The distance ( r ) between the BSA (donor) and ISO (acceptor) was 2.89 nm, determined by FRET. DLS measurements interpreted complex formation due to the reduction in hydrodynamic radii of the protein in the presence of the drug. The binding site of ISO was found to be nearer to Trp 134 with the help of molecular docking and the Δ G ° was found to be –10.2 kcal mol −1 . The esterase activity result suggests that ISO acts as competitive inhibitor. Thus, this study would help to determine the binding capacity of the drug to the protein which may indicate the efficiency of diffusion of ISO into the blood for the treatment of heart diseases.